The EC′ mechanism: Split waves at the channel electrode - Fisher, A; Compton, R (1992)
A computational strategy is presented for the simulation of current-voltage curves of electrode processes with very fast coupled homogeneous kinetics at the channel electrode. The approach is illustrated by consideration of the EC' mechanism that relates to the homogeneous catalysis of electrochemical reactions. It is shown that for fast catalytic reactions "split" voltammetric waves are observed where the two components of the wave result first from the direct reduction (oxidatio